Secondary metabolites of the invasive tree, Callery pear (Pyrus calleryana), provide support for the empty niche theory of invasion - Jessica A. Hartshorn (PLoS ONE, 2025)
Invasive woody species like Callery pear (Pyrus calleryana Decne.) alter ecosystems directly and indirectly through effects on arthropod communities as well as chemical alterations of the soil. Evidence suggests that the aggressive spread and negative impacts are due to allelopathic chemicals present throughout plant tissues which reduce herbivory and add unique allochthonous inputs to the soil, thereby reducing germination of native species and furthering Callery pear’s domination on the landscape. To assess the allelopathic potential of Callery pear, we collected leaf tissue from Callery pear, black cherry (Prunus serotina) as the native comparison, and wild peach (Prunus persica) to serve as a non-native but non-invasive representative. Callery pear leaves contained 32 unique compounds compared to our other two species tested, with 23 of these compounds belonging to the group of compounds called flavones, which are secondary metabolites known to build up in the roots of plants and cause autotoxicity, along with changes to the soil microbial community, including mycorrhizal fungi. While flavones are ubiquitous in nature, their presence in Callery pear suggests downstream effects on native plants and arthropod communities, and provides evidence for the empty niche theory of invasion. Further experiments are needed to confirm flavones in other Callery pear tissues and to assess the mediating chemical pathways that lead to their upregulation.